The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/cts.12953
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection as a trigger of autoimmune response

Abstract: Currently, few evidences have shown the possible involvement of autoimmunity in patients affected by coronavirus disease 2019 (COVID‐19). In this study, we elucidate whether severe acute respiratory syndrome coronavirus disease 2 (SARS‐CoV‐2) stimulates autoantibody production and contributes to autoimmunity activation. We enrolled 40 adult patients (66.8 years mean age) admitted to Alessandria Hospital between March and April 2020. All the patients had a confirmed COVID‐19 diagnosis and no previously clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
2
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 27 publications
(39 reference statements)
9
109
2
10
Order By: Relevance
“…Increased autoantibodies have been demonstrated in COVID19 patients (8,9). Recently, neutralizing IgG antibodies against several types of interferon were found in life-threatening COVID19, while no such autoantibodies were found in individuals with mild disease (10).…”
Section: Discussionmentioning
confidence: 99%
“…Increased autoantibodies have been demonstrated in COVID19 patients (8,9). Recently, neutralizing IgG antibodies against several types of interferon were found in life-threatening COVID19, while no such autoantibodies were found in individuals with mild disease (10).…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) has similarities to systemic autoimmune conditions, including an association with increased incidence of autoantibodies [1][2][3], including those directed toward cytokines [4]. However, reports to date lack longitudinal assessments and have inadequate controls (i.e., comparison to different severities within COVID-19 or to healthy individuals).…”
Section: Dear Editormentioning
confidence: 99%
“…We analyzed disease severity and presence of AAB in 22 COVID + and 20 COVID -ICU patients with respiratory distress of similar severity, enrolled contemporaneously, over time. We used HEp2 IFA to typify ANAs, as well as solid-phase multi-analyte arrays and bead-based multiplexed immunoassays to typify specific autoreactive antigens such as those observed in autoimmune diseases such as systemic lupus erythematous, Sjögren syndrome, systemic sclerosis, autoimmune inflammatory myopathies, and others [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…A significant limitation of studies that have reported the emergence of autoantibodies (AAB) in COVID-19 4, 6, 10 has been the lack of control groups with similar clinical characteristics and the lack of longitudinal data monitoring the development of autoimmunity over time. Our study provides evidence that, when observed longitudinally, severe COVID-19 patients have similar AAB prevalence as a control cohort of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation